Improving emotional availability in Australian mother-toddler dyads via the Tuning in to Toddlers parenting program - Zoe C. G. Cloud; Christiane E. Kehoe; Karli Treyvaud; Bradley Wright; Sophie S. Havighurst (Scientific Reports)
Abstract This study examined whether an emotion socialisation parenting program, Tuning in to Toddlers (TOTS), contributed to observed improvements in mother-toddler emotional availability. Parents of toddlers aged 18–36 months were recruited through childcare centres and maternal child health centres in Melbourne, Australia and were allocated to either an intervention or a waitlist control condition in a cluster-randomised controlled design. Parents in the intervention condition participated in 6 group sessions of TOTS. Baseline and 12-month follow up observation assessments for 99 mother-toddler dyads (intervention, n = 50; control, n = 49) were coded using the Emotional Availability Scales (4th edition) and analysed for between-group differences and clinically reliable change. Compared with the control condition, mothers in the intervention condition showed significant improvements in maternal sensitivity (p = 0.004). Further, significantly more intervention dyads reliably improved on maternal structuring (p =0 .013) and child responsiveness (p =0 .042), whereas those who received no intervention reliably deteriorated on maternal sensitivity (p = 0.001) and non-intrusiveness (p = 0.040). Thus, the preliminary evidence from this study indicates that an emotion socialisation program delivered to parents of toddlers may influence emotional availability.